THE ROLE OF CORPORATE CULTURE IN BUSINESS EFFECTIVENESS - Kvirkvaia, Murtaz; Kikutadze, Vasil (European Scientific Journal, ESJ, 2014)
Organizations execute a lot of unavoidable changes while developing, and their main purpose is an organizational restructuring and reaching and using the methods and tools, which implement the effectiveness of development. In the conditions of cutthroat competition companies have to struggle for every customer, that’s why they should analyze the processes in the market and in company intensively, companies should work out facility in forming innovations and in using its potential. The company’s potential in that direction is realized by “the corporate culture”. The corporate culture is the system of organizational employees’ activity, moral values, behavior rules and standards, which helps employees in doing their business effectively and satisfy their own interests. The corporate culture is the most effective opportunity for manager’s relief; it conditions the existence of organization in the best way, creates corporate standards, ensures corporate employees in correctness of these goals and standards and introduces the mechanism of values passing. Though, it’s natural, that the corporate culture cannot bring profit and income for organization, hence it follow that it’s important to realize aimed stepwise actions to form healthy corporate culture in the organization.